Lantunan Masa Kecil dalam â€œLullabybianuâ€ - Komang Wira Adhi Mahardika (Journal of Music Science, Technology, and Industry, 2018)
â€œBibi Anuâ€//Lamun payu luas manjus/Antenge tekekang//Yatnain ngabe masui//Tiyuk puntul//Bawang anggen sasikepan. The folk song which has deep meaning and full of messages is always ringing in the hearts of Balinese children. Moreover, mother's love for her beloved child in simple lyrics and tones in the "Bibi Anuâ€ indicates that every child should always be alert, preparing for every circumstances. However, today, the song is getting drowned, considered obsolete and is marginalized. There is an impression that singing traditional songs such as "Bibi Anu" is regarded out of date so that such kind of song is not favoured anymore. In social media which develop rapidly, traditional songs such as "Bibi Anu" are rarely seen. Therefore, the composer wants to compose it newly, into a project named "Lullabybianu", i.e. from the words lullaby and "Bibi Anu". Lullaby is a universal song sung for children. This project is a form of presentation of the musical composition that comes from the desire of the composer to pick a traditional childhood's song in Bali, especially pupuh pucung into a new musical work performed with a combination of Western and Balinese musical instruments. In this case, the composer combines Western and Balinese music through an ansamble of cello, piano, saxophone, percussion combined with gender rambat traditional instrument, flute, and vocals. "Lullabybianu" is composed basing on the musical science of harmony and other musical theories in which there are special rules that bind so that the notation of this work will be good and true.